P186Sphingomyelinase induces nitric oxide and hydrogen sulfide dependent vasorelaxation in db/db mice. (15th July 2014) - Kiss, L; Straky, ZS; Korda, D; Parkanyi, A; Ruisanchez, E; Benyo, Z
Abstract: Purpose: It was shown earlier by our group and others that sphingomyelinase (SMase) induces changes of vascular tone with an initial contraction and subsequent relaxation in aortic rings of wild type mice. Sphingolipids are essential components of cell membranes and sphingolipid metabolites have been implicated as important regulators in diabetes. Thus, we aimed to investigate the vascular effects of SMase in a mouse model of diabetes and to elucidate the involved potential mediators and signal transduction pathways. Methods: Thoracic aorta segments were isolated from adult db/db and non-diabetic littermate mice. The effect of 0.2 U/ml SMase was investigated after precontraction with 0.1 μM phenylephrine under isometric conditions in myographs. Vascular segments were also tested in the presence of the following inhibitors: eNOS inhibitor L-NAME (100 μM), selective thromboxane receptor antagonist SQ 29, 548 (1 μM), ceramidase inhibitor D-erythro-MAPP (50 μM), PI3-kinase inhibitor Wortmannin (0.1 μM), Akt-inhibitor MK2206 (1 μM) and cystathionine-γ-liase (CSE) inhibitor propargylglycin (10 mM). Results are expressed as percentage changes compared to the tone of precontraction. Results: SMase evoked an initial contraction in control vessels (13.8±6.3%) followed by relaxation to the original tone, while it caused a marked relaxation in the diabetic vessels (-21.9±7.1%). L-NAME administration further increased the contraction in the control (25.3±7.6%) and contraction occured in the diabetic vessels as well (36.8±3.1%). SQ 29, 548 led to relaxation in both groups, but these were more pronounced in the db/db group (-25.1±6.3% vs. -63.1±14.9%). Co-administration of the inhibitors caused no change in vascular tone after SMase treatment. The use of D-erythro-MAPP, Wortmannin and MK2206 did not alter the vasoactive effects of SMase in any group, but propargylglycin decreased the SMase induced vasorelaxation (-22.02±4.95%, p<0.05) in diabetic vessels. Conclusions: SMase induces biphasic changes in the tone of db/db mice derived vessels and these effects are mediated by thromboxane A2 and endothelial nitric oxide. Importantly, the relaxations are enhanced in diabetic vessels, which is a surprising and novel phenomenon. Our finding that CSE plays a profound role in these enhanced relaxations may provide a possible explanation to this. CSE produces hydrogen sulphide, a novel gasotransmitter that can inhibit phosphodiesterase in smooth muscles leading to higher levels of cGMP, thus relaxation. Our results may indicate a novel possibility to enhance vasorelaxation in diabetes by SMase via hydrogen sulphide signaling.